NTRK Gene Expression Analysis in Oral Squamous Cell Carcinoma Mexican Population - Lilibeth Stephania Escoto-Vasquez; Javier Portilla-Robertson; Josué Orlando Ramírez-Jarquín; Luis Fernando Jacinto-Alemán; Alejandro Alonso-Moctezuma; Carla Monserrat Ramírez-Martínez; Osmar Alejandro Chanes-Cuevas; Fabiola Salgado-Chavarria (MDPI AG, 2024)
Oral cancer holds the sixth position in malignancies worldwide; 90% correspond to oral squamous cell carcinoma (OSCC). Diverse reports suggest that NTRK genes and their receptors are key oncogenesis regulators to tumor progression in human cancers. Objective: To analyze the NTRK and Trk expression and their association with clinicopathological features of OSCC in Mexican patients' samples. Material and Methods: We analyzed 95 OSCC cases of pan-trk immunoexpression through a software-assisted method. Gene expression was analyzed by RT-qPCR employing the ΔΔCT method. Kruskal-Wallis and Spearman's correlation tests were performed. Results: Our mean age was 62.4 (±16.9) years. A total of 37 cases were tumors in the lateral border of the tongue. Age was significantly associated with the anatomical site. 42% (40 of 95) cases were pan-trk positive. A total of 21 cases showed intense immunoexpression predominantly in poorly differentiated OSCC, with a significant correlation between immunoexpression and age and gender. Gene expression showed that poorly differentiated cases exhibited higher NTRK2 expression, while well-differentiated cases demonstrated NTRK3 significantly higher expression. Conclusions: Our results suggest that NTRK family expression is present in OSCC, with differential expression related to differentiation degree. Additional information about their activation or mutational status could reinforce their potential as a possible primary or adjuvant treatment target.